PERANCANGAN DAN IMPLEMENTASI JARINGAN VLAN BERBASIS MIKROTIK DI PT. BATAM CIPTA INDUSTRI - Hansen, Irvan (National Conference for Community Service Project (NaCosPro), 2025)
Unstructured computer networks often lead to problems such as IP conflicts, unstable connections, and lack of user segmentation. PT. Batam Cipta Industri experienced these issues due to its conventional system without centralized network management. This community service project involved designing and implementing a VLAN-based network using Mikrotik RouterOS. The activity stages included network observation, configuration simulation using pNetLab, and direct implementation in the office. Each entity within the building—BCI, WPRP, and SDCA—was assigned a dedicated VLAN segment with separate DHCP servers and gateways. The implementation results showed successful IP assignment, more stable internet connection, and isolated communication across VLANs. This activity had a direct impact on improving network efficiency and serves as a simple model for SME-scale network design. Further recommendations include integrating firewall systems and bandwidth management tailored to each entity’s needs.